Regulasi Emosi dan Kepribadian Introvert: Faktor Penentu Self Injury di Kalangan Mahasiswa di Surabaya - Setyawan, Riko Yuli; Pratikto, Herlan; Aristawati, Akta Ririn (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Students are expected to have good critical thinking and problem solving skills, but in reality some of them still commit self injury as a way to relieve or divert the emotional pain they feel. This study aims to determine whether there is a relationship between emotion regulation and introverted personality tendencies with self injury tendencies in university students in Surabaya. Correlational quantitative research method with the number of respondents as many as 384 students who were taken using purposive sampling technique. The analysis in this study used multiple linear regression analysis. The results showed that there is a significant relationship between emotion regulation and introverted personality tendencies with self injury tendencies in university students in Surabaya. Students with low emotion regulation and high introverted tendencies tend to have a greater risk of self injury. This research provides important insights in efforts to prevent and intervene in self injury behavior through improving emotion regulation and understanding individual personality types.